PROSES PENYELESAIAN MASALAH BERDASARKAN TAHAPAN POLYA DITINJAU DARI TIPE KEPRIBADIAN SISWA KELAS XI SMA - Octaviani, Christina; Hartoyo, Agung; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research discuss about problem solving process of average calculated at class XI senior high school students that have sanguinis personality type and melancholy personality type based on Polya?s stage. The method used was descriptive method and this research form was case study. Research subject was eight students, with four students for every personality type. To collect data used questionnaire, problem solving test and completed with interview. Data analysis used qualitative analysis technique based on personality type and analysis guidlines of problem solving process that reffered at Polya stage. Research result showed that students who have sanguinis personality type understood problem well although did not write it, made solving plan but did not write it explicitly but explained their mind directly to answered the problem, applied the solving plan and checked the answer again. Students who have melancholy personality typed could write their understanding, wrote the things known and the things asked, then made problem solving plan in writing and  did the solving plan. At the last stage, students could rechecked their answer.   Keyword: Problem Solving, Polya Stages, Personality Type